Muslim Women and Gender: Culture Vs. Divine Text - Abdel-Hady, Zakaryya Mohamed Ahmed (European Scientific Journal, ESJ, 2017)
Much confusion have developed on the issue of Islam and gender. Islam as a religion is seen to give preference to one gender over the other. This has been particularly realized in dealing with issues which are of concern to women such as: duties and responsibilities of both husband and wife and inheritance. The issue of gender will always raise the question of Muslim Women’s full participation and productive functioning within the society. This paper attempts to examine whether the above-mentioned issue is a simple misconception, or the existence of any evidence within the Muslim doctrine and/or interpretation of Muslim scholars that support such a claim. The issues discussed here are highly controversial and debatable. Thus, in order to identify and clarify the stance of Islam on the issue of gender, we undoubtedly need to revisit the Islamic sources and hold a comparison to social and historical events that took place within the early Muslim society. This paper aims to highlight this issue and attempt to identify whether any validation for such practice was made within the religious approach or through traditionally-acquired concepts that have lived and grew within the Muslim cultures throughout the ages.